Achieving food security in Ghana: Does governance matter? - Peter Asare-Nuamah; Anthony Amoah; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
This study complements the extant literature by assessing the role of governance dynamics in food security in Ghana for the period 1980-2019. The empirical evidence is based on the Fully Modified Ordinary Least Squares (FMOLS) technique and governance is categorized into: political (entailing political stability and voice & accountability), economic (consisting of regulatory quality and government effectiveness) and institutional (entailing corruption-control and the rule of law) governance dynamics. The study finds that the engaged governance dynamics improve food security in Ghana. Policy implications are discussed with specific emphasis on the sustainable development goals.
Keywords: I38; Q12; R20; O20; O55; 330; Governance; Vulnerability; Food security; Sustainable development